A study on the volatile oil of Illicium anisatum Linn. - Wungwira, Linchee 1936-
The air-dried fruits of Illicium anisatum Linn. (Sanke) yielded 7.48% of the volatile oil by water distillation. The physical and chemical properties of the oil were determined. The oil was fractionated and its constituents were determined by preparing derivatives, using gas chromatography, thin-layer chromatography and infrared spectrophotometry. The main constituent found was anethole. P-cymene and phellandrene were also present. The results of the experiment show that the sample of Illicium anisatum L. sold in the market as sanke is Illicium verum Hook f. () (fam. Magnoliaceae), the non-poisonous variety.